Penerapan Kursi Ergonomis Dan Peregangan Untuk Mengurangi Keluhan Nyeri Punggung Pada Pekerja Di Industri PT. “X” Kebumen Jawa Tengah - Yuliana Yuliana; Yamtana Yamtana; Achmad Husein (POLTEKKES KEMENKES YOGYAKARTA, 2019)
Ergonomics plays an important role in improving occupational safety and health factors. Workers knitting in the Prembun false eyelash industrydo the work manually in a sitting position on an elongated chair without a backrest so that the buttocks don't hurt when sitting too long, bending forward and repetitive hand movements. The purpose of this study was to determine the effect of ergonomic chairs and stretches to reduce complaints of back pain in workers at PT X.Thistype of research is quasi-experimental (quasi experiment) with the approach pretest posttest group design. The sample of this study was 23 workers, taken by purposive sampling technique.The measurement method used the questionaire Nordic Body Map to find out the number of complaints of back pain. Test the normality of the data using the Shapiro-Wilk test then followed the bound t-test, at ? = 0.05.The average decrease in back pain complaints was 10.39 or 37.11%,11.89 or 33.23%, and 4.91 or 17.54%. Data were analyzed using t-test bound obtained p-value =0.000 or p<0.05 indicates there is a significant effect on the reduction of back pain complaints of respondents in using ergonomic chair and stretching in the industry of false eyelashes PT X.